Development of Android-Based Interactive Learning Media to Improve Students’ Reading Abilities at SDI Kondamara 2 - Yunarti Raji Roy; Fajar Hariadi; Novem Berlian Uly (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
This research focused on creating an innovative Android-based interactive learning media designed to enhance reading comprehension among first-grade students. The development process employed Unity 3D, a powerful platform for creating engaging digital applications, combined with the Model Development Life Cycle (MDLC) method to ensure a systematic and structured approach. To add an element of variability and challenge, the Learning Content Generator (LCG) algorithm was integrated into the media, enabling the randomization of quiz questions. This feature aimed to prevent predictability and encourage critical thinking among young learners. The implementation of this interactive media was tested in a classroom setting, and the results were highly encouraging. The students demonstrated a significant improvement in their reading comprehension skills, with scores increasing by 62.8% from the initial pre-test to the subsequent post-test. This substantial gain indicates that the use of technology-enhanced learning tools, particularly those incorporating game-like elements and adaptive algorithms, can effectively support early literacy development. Overall, this study highlights the potential of combining Unity 3D, the MDLC method, and the LCG algorithm to create impactful educational media for young learners.